Ubiquitin over-expression phenotypes and ubiquitin gene molecular misreading during aging in Drosophila melanogaster. - Hoe, N.; Huang, C.M.; Landis, G.; Verhage, M.; Ford, D.; Yang, J.; van Leeuwen, F.W.; Tower, J. (Aging, 2011)
Molecular Misreading (MM) is the inaccurate conversion of genomic information into aberrant proteins. For example, when RNA polymerase II transcribes a GAGAG motif it synthesizes at low frequency RNA with a two-base deletion. If the deletion occurs in a coding region, translation will result in production of misframed proteins. During mammalian aging, misframed versions of human amyloid precursor protein (hApp) and ubiquitin (hUbb) accumulate in the aggregates characteristic of neurodegenerative diseases, suggesting dysfunctional degradation or clearance. Here cDNA clones encoding wild-type hUbb and the frame-shifted version hUbb(+1) were expressed in transgenic Drosophila using the doxycycline-regulated system. Misframed proteins were abundantly produced, both from the transgenes and from endogenous Drosophila ubiquitin-encoding genes, and their abundance increased during aging in whole-fly extracts. Over-expression of wild-type hUbb, but not hUbb(+1), was toxic during fly development. In contrast, when over-expressed specifically in adult flies, hUbb(+1) caused small decreases in life span, whereas hUbb was associated with small increases, preferentially in males. The data suggest that MM occurs in Drosophila and that the resultant misframed proteins accumulate with age. MM of the ubiquitin gene can produce alternative ubiquitin gene products with different and sometimes opposing phenotypic effects.